Bioconversion and quantification of humic substances from low rank coals using indigenous fungal isolates. (20th November 2022) - Rehman, Muhammad Zia ur; Akhtar, Kalsoom; Khan, Ali Nisar; Tahir, Muhammad Ali; Khaliq, Shazia; Akhtar, Nasrin; Ragauskas, Arthur J.
Abstract: The major portion of coals around the world belongs to lignitic origin, and burning of these Low Rank Coals (LRCs) not only produces energy, but also release harmful gases into the environment. On the other hand, coal is a mega source of fossilized carbon compounds that can be utilized in diverse range of carbon/organic industries. Biosolubilization is one of the safest and economical way to consume these LRCs for the harvest of humic and fulvic acids for industrial applications. Present studies deal with solubilization of coal samples from five different mines of Punjab, Pakistan by indigenously isolated fungus. From a number of indigenously isolated fungal isolates, an isolate NF-2 was selected based on its solubilization potential on solid Sabouraud medium. The intensity of coal biosolubilization was found maximum for coal sample B-1 (59%) and lowest for sample B-26 (17.2%) with 5% (w/v) pulp density at 28 ± 2 °C. Humification index value (A4 /A6 ) for biosolubilized products of coal sample B-1 was found 6.18 which was much higher than the A4 /A6 value (4.27) of commercially available standard humic acid. Biosolubilized products from coal sample B-1 was found maximum with 8681 mg/L humic acid concentration as determined by standard curve method. FTIR and FE-SEM analyses of sample B-1 treated with NF-2 confirmed the structural break down and solubilization of coal. Molecular identification of fungal isolate NF-2 showed 100% similarity to Aspergillus flavus . This work paves the way to utilize lignitic coals for the environment friendly and low-cost production of humic acids by fungal biosolubilization as an alternate to chemical methods. Graphical abstract: Image 1 Highlights: Coal samples from salt range of Pakistan were characterized and identified as lignitic in origin. Amomg indigenous fungal isolates, NF-2 (identified as A . flavus ) showed efficient coal bioconversion/biosolubilization. Aspergillus flavus showed 59% bioconversion/biosolubilization of coal sample B-1 in submerged fermentation. Quantification of humic acid in biosolubilized coal products by standard curve method gave a value of 8681 mg/L. FTIR and FE-SEM analyses revealed significant differences in fungal treated/untreated and bio-solubilized products of coal.